Tubular peroxisomes in HepG2 cells: Selective induction by growth factors and arachidonic acid - Schrader, Michael; Krieglstein, Kerstin; Fahimi, H. Dariush (European journal of cell biology, 1998)
We showed recently the plasticity of the peroxisomal compartment in the human hepatoblastoma cell line HepG2 as evidenced by the presence of elongated tubular peroxisomes measuring up to 5 μm next to much smaller spherical or rod-shaped ones (0.1-0.3 μm). Since the occurrence of tubular peroxisomes in a given cell in culture is synchronized, with neighboring cells containing either small spherical or elongated tubular peroxisomes, cell counting of immunofluorescence preparations stained for catalase was used for the quantitative assessment of the dynamics of the peroxisomal compartment and the factors regulating this process. Initial studies revealed that the formation of tubular peroxisomes is primarily influenced by the cell density as well as by lipid- and protein-factors in fetal calf serum, being independent of an intact microtubular network. Biochemical studies showed that the occurrence of tubular peroxisomes correlated with the expression of the mRNA for 70 kDa peroxisomal membrane protein (PMP70), but not with that of matrix proteins. By cultivation of cells in serum-and protein-free media specific factors were identified which influenced the formation of tubular peroxisomes. Among several growth factors tested, nerve growth factor (NGF) was the most potent one inducing tubular peroxisomes and its effect was blocked by K252b, a specific inhibitor of neurotrophin receptor pathway, suggesting the involvement of signal transduction in this process. Furthermore, from several polyunsaturated fatty acids (PUFA) which all induced tubular peroxisomes, the arachidonic acid (AA) was the most potent one. Our observations suggest that tubular peroxisomes are transient structures in the process of rapid expansion of the peroxisomal compartment which are induced either by specific growth factors or by polyunsaturated fatty acids both of which are involved in intracellular signaling.